Comparison of cardiac volumetry using real-time MRI during free-breathing with standard cine MRI during breath-hold in children. - Röwer, Lena Maria; Radke, Karl Ludger; Hußmann, Janina; Malik, Halima; Uelwer, Tobias; Voit, Dirk; Frahm, Jens; Wittsack, Hans-Joerg; Harmeling, Stefan; Pillekamp, Frank; Klee, Dirk (Pediatric Radiology, 2022)
Background: Cardiac real-time magnetic resonance imaging (RT-MRI) provides high-quality images even during free-breathing. Difficulties in post-processing impede its use in clinical routine.Objective: To demonstrate the feasibility of quantitative analysis of cardiac free-breathing RT-MRI and to compare image quality and volumetry during free-breathing RT-MRI in pediatric patients to standard breath-hold cine MRI.Materials and Methods: Pediatric patients (n = 22) received cardiac RT-MRI volumetry during free breathing (1.5 T; short axis; 30 frames per s) in addition to standard breath-hold cine imaging in end-expiration. Real-time images were binned retrospectively based on electrocardiography and respiratory bellows. Image quality and volumetry were compared using the European Cardiovascular Magnetic Resonance registry score, structure visibility rating, linear regression and Bland-Altman analyses.Results: Additional time for binning of real-time images was 2 min. For both techniques, image quality was rated good to excellent. RT-MRI was significantly more robust against artifacts (P < 0.01). Linear regression revealed good correlations for the ventricular volumes. Bland-Altman plots showed a good limit of agreement (LoA) for end-diastolic volume (left ventricle [LV]: LoA -0.1 ± 2.7 ml/m2, right ventricle [RV]: LoA -1.9 ± 3.4 ml/m2), end-systolic volume (LV: LoA 0.4 ± 1.9 ml/m2, RV: LoA 0.6 ± 2.0 ml/m2), stroke volume (LV: LoA -0.5 ± 2.3 ml/m2, RV: LoA -2.6 ± 3.3 ml/m2) and ejection fraction (LV: LoA -0.5 ± 1.6%, RV: LoA -2.1 ± 2.8%).Conclusion: Compared to standard cine MRI with breath hold, RT-MRI during free breathing with retrospective respiratory binning offers good image quality, reduced image artifacts enabling fast quantitative evaluations of ventricular volumes in clinical practice under physiological conditions.